2006
DOI: 10.1590/s0101-31222006000200016
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de sementes de couve brócolis beneficiadas em mesa densimétrica

Abstract: , ORLANDO ANTÔNIO LUCCA FILHO 4 , FRANCISCO AMARAL VILLELA 4 RESUMO -Os resultados de pesquisas desenvolvidas demonstram a eficiência da mesa densimétrica no aprimoramento da qualidade de sementes de diversas espécies, evidenciando superioridade da qualidade fisiológica e sanitária das sementes coletadas nas posições superiores em relação às posições inferiores da zona de descarga da mesa. Considerando o reduzido número de trabalhos publicados sobre beneficiamento de sementes de hortaliças em especial sob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
5
0
5
Order By: Relevance
“…Thus, similar results were observed for corn seeds (Ferreira & Sá, 2010), broccoli (Gadotti et al, 2006) and fodder radish (Nery et al, 2009).…”
Section: Resultssupporting
confidence: 83%
“…Thus, similar results were observed for corn seeds (Ferreira & Sá, 2010), broccoli (Gadotti et al, 2006) and fodder radish (Nery et al, 2009).…”
Section: Resultssupporting
confidence: 83%
“…Gadotti et al (2006) observed that seed germination and vigor in cabbage-brocolli increased when they originated from the upper outlets of the densimetric table. Means followed by the same letter in the column do not differ between themselves at the 5% significance level using the Scott-Knott test.…”
Section: Resultsmentioning
confidence: 99%
“…The separation of seeds on a densimetric table has been efficient for improving the seed lot quality of various species (Nascimento et al, 1994;Possenti et al, 1997;Alexandre and Silva, 2000;Fantinatti et al, 2002;Gadotti et al, 2006;Mertz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These damages are usually from the process of seed formation, resulting in seeds empty, wrinkled and of smaller size and weight. It is noteworthy that such differences allow that seeds attacked by fungi can be eliminated from the batch, enabling not only the improvement of health quality, as well as the physiological quality of the seed lot (GADOTTI, 2006).…”
Section: Introductionmentioning
confidence: 99%